Effect of elevated carbon dioxide levels on growth and biochemical composition of selected microalgae / Saraswathy d/o Ramachandran - Ramachandran, Saraswathy (2012)
The fixation of carbon dioxide by microalgae plays a major role in mitigation of carbon dioxide in the atmosphere as it can reduce the “Greenhouse” effects. In this study, ten strains of microalgae from the University of Malaya Algae Culture Collection (UMACC) were used for selection of potential strains with high biomass, lipid, protein and carbohydrate productivity. The microalgae screened included freshwater and marine strains including one isolated from palm oil mill effluent (Chlorella UMACC 275). The microalgae strains were grown in flask cultures for 12 days in batch culture with continuous aeration from an aquarium air-pump. Of the microalgae screened, Chlorella vulgaris UMACC 001 produced highest biomass 240.67±5.77mg/l and lipid 38.67± 4.62% DW with 69.36±4.103% DW protein and 1.92±0.177% DW carbohydrate. The specific growth rate (μ) of Chlorella vulgaris UMACC 001 attained was 0.2433±0.0168day-1. Besides, Scenedesmus quadricauda UMACC 041, Chlorella UMACC 275 and Oocystis UMACC 074 also produced relatively higher biomass, lipid, protein and carbohydrate content compared with other strains studied. All the four strains were grown at carbon dioxide levels ranging from 0.04%, 5% to10% for 10 days in batch culture on 12:12 h light-dark cycle. Chlorella vulgaris UMACC 001 showed maximum specific growth rate, 0.3707±0.0171day-1 at 5% CO2. It also produced significant biomass of 268.67±22.030mg/L (p<0.05), lipid 34.58±1.140%DW (p<0.05), protein 59.44±3.905% DW (p<0.05) and carbohydrate 1.37±0.104% DW (p<0.05) content. Chlorella UMACC 275 attained higher biomass 146±9.165mg/L and lipid content 31.05±5.703% DW (p<0.05) with 53.59±2.20% DW (p<0.05) protein and 1.85±0.137% DW (p<0.05) carbohydrate content at 10% CO2 although the production was less than Chlorella vulgaris UMACC 001. Scenedesmus quadricauda UMACC 041 produced higher biomass 257.33±56.757mg/L (p<0.05) but lower lipid content 28.48±6.884%DW with 52.803±2.001% DW (p<0.05) protein and 1.19±0.030% DW iv (p<0.05) carbohydrate content at 5% CO2. Therefore, Chlorella vulgaris UMACC 001 was shown to be a potential strain for mitigating carbon dioxide and as a feedstock for biofuel as it produces high amounts of lipid, protein and biomass.